THE PROBLEM OF EDUCATION FIGHTERS' SENSE OF INJUSTICE IN THE EDUCATION SYSTEM IN INDONESIA - Yuliana Sri Purbiyati; Eko Armada Riyanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Teachers or education fighters, especially honorary teachers in Indonesia do not yet have regulations. This causes honorary teachers to experience a sense of injustice in terms of income or income. As many as 48% of the total teacher population are non-civil servant teachers, most of whom earn below the regional minimum wage. The focus of this research is how to use existing resources to fight for the problem of a sense of injustice for honorary teachers to their income based on the philosophy of relationality. The aim is to explore or explore in more detail the opportunities and challenges of using resources to achieve a sense of justice for honorary teachers in their income. This research is a literature study, with qualitative methods and a relational philosophy approach. The result of this research is that the President is central to solving the problem of honorary teachers because the Indonesian government system is presidential so that the president becomes the head of state as well as the government. The Indonesian government should have drawn up a grand design for the field of education, specifically for human resources, by removing the status of civil servant and non-civil servant teachers and their derivatives so that there is only one term for teachers of the Republic of Indonesia who have the same regulations, welfare and guarantee of work wherever they carry out their duties. in both public and private schools. Keywords: honorary teacher, sense of justice, welfare, resources, government